2016
DOI: 10.1159/000447433
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D<sub>3</sub>-Supplemented Yogurt Drink Improves Insulin Resistance and Lipid Profiles in Women with Gestational Diabetes Mellitus: A Randomized Double Blinded Clinical Trial

Abstract: Background: Our study aimed to examine the effects of daily consumption of vitamin D3-supplemented yogurt (VDY) drink on insulin resistance and lipid profiles in pregnant gestational diabetes mellitus (GDM) patients. Methods: Participants aged 24-32 years in their second trimester were randomly assigned to consume either plain yogurt or VDY daily for 16 weeks. Metabolic and lipid profiles including levels of fasting plasma glucose (FPG), serum insulin, triacylglycerol (TAG), total cholesterol (TC) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 24 publications
1
57
2
Order By: Relevance
“…In the studies done by Li et al [32] and Valizadeh et al [31] where the investigators used a block randomization method, the risk of selection bias was low.…”
Section: Risk Of Bias In Articlesmentioning
confidence: 98%
See 4 more Smart Citations
“…In the studies done by Li et al [32] and Valizadeh et al [31] where the investigators used a block randomization method, the risk of selection bias was low.…”
Section: Risk Of Bias In Articlesmentioning
confidence: 98%
“…Finally, fulltext review of collected studies indicated that a total of 5 RCTs met all the inclusion criteria and could be retained for meta-analysis: Asemi et al [29], Asemi et al [30], Valizadeh et al [31], Li et al [32], and Yazdchi et al [33] (Figure 1). …”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 3 more Smart Citations